The Theory of the National-Cultural Autonomy in the Armenian Social-Philosophical Thought at the Beginning of the 20th Century - Zakaryan, Seyran (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
The Armenian theorists, representing different parties of the beginning of the 20th century, when discussing the role of the nations in a state, especially the question of the legalpolitical status of the Armenians, used to point out four options: independence, federation, national-territorial and national-cultural autonomy. The Hunchakian theorists (S. Sapah- Gyulian), discussing several types of autonomy, at the end defended the idea of independent Armenia, suggesting the unification of the divided parts of Armenia into one state. The ideologists of the A.R Federation (G. Khajak, M. Vardanyan) used to defend the national-territorial and national-cultural theories of autonomy, thinking that firstly they are advantageous to those nations, especially to the Armenians, who have a national territory in a state and are spread around the country at the same time, and secondly, that they are the ideal form of solving the national question which is creating a federal state. The ‘Specifists’ (D. Ananun, B. Ishkhanyan) thought that the Armenians could only have national-cultural autonomy because they were never the majority among the population of neither the Russian, nor the Turkish states. The Armenian Marxists, (St. Shahumyan, Al. Myasnikyan and others) considering the class to be superior to the nation and opposing class unification to that of the nation, were against not only the independence of Armenia, but also to the national-territorial and nationalcultural theories. According to them there should be neither national-cultural, nor national-territorial divisions as they would interfere in the class fight and oppose the interests of the proletariat. According to the author the theory of the national-cultural autonomy had two meanings: positive, because it was a legal means to unite the national force and maintain the national identity. It would be negative at the same time if the theory is limited by national-cultural autonomy as it would ignore the existence of the historical Homeland, the national territory without which it is impossible to imagine the physical and spiritual existence and of a nation and provide its security and the possibility of obtaining any legal- political status in the future.